Wheelchair controller by eye motion using Emotive Epoc neuroheadset - Ghayadah, Iman; Almhareeq, Arkan; Baniodeh, Afnan (جامعة بوليتكنك فلسطين - هندسة حاسوب, 2021)
To be fair in a humane society, Handicapped people need to live more normal life as possible as we can.Adjusting to life with a disability can be a difficult transition..It’s possible to overcome the challenges they face and enjoy a full and fulfilling life as there are many ways to improve their indepence and the sense of empowerment. In this project,we design a wheelchair controller system which is used for reading eye movement of handicapped people with complete disability. The system will be designed to read the movement of the eye using the helmet which allows the chair to move in the right direction.If something wrong for example, he falls, the system sends an alarm to the patient's relatives. The system will also be able to detect obstacles and change it’s direction left or right . At the end of the project, we did two things. First, the handicapped people will be able to control the movement of their wheelchair safely using the eye movement.Second, the chair will react and move in the required direction.
no of pages 50 , هندسة حاسوب 11/2021
Keywords: Wheelchair controller; Emotive Epoc; neuroheadset